Minimum Eccentricity Shortest Path Problem with Respect to Structural Parameters - Kučera, Martin; Suchý, Ondřej (Algorithmica, 2023)
The Minimum Eccentricity Shortest Path Problem consists in finding a shortest path with minimum eccentricity in a given undirected graph. The problem is known to be NP-complete and W[2]-hard with respect to the desired eccentricity. We present fpt-algorithms for the problem parameterized by the modular width, distance to cluster graph, the combination of treewidth with the desired eccentricity, and maximum leaf number.